Flow of granular matter in a silo with multiple exit orifices: jamming to mixing - Kamath, Sandesh; Kunte, Amit; Doshi, Pankaj; Orpe, Ashish V. (Physical Review E, 2014)
We investigate the mixing characteristics of dry granular material while draining down a silo with multiple exit orifices. The mixing in the silo, which otherwise consists of noninteracting stagnant and flowing regions, is observed to improve significantly when the flow through specific orifices is stopped intermittently. This momentary stoppage of flow through the orifice is either controlled manually or is chosen by the system itself when the orifice width is small enough to cause spontaneous jamming and unjamming. We observe that the overall mixing behavior shows a systematic dependence on the frequency of closing and opening of specific orifices. In particular, the silo configuration employing random jamming and unjamming of any of the orifices shows early evidence of chaotic mixing. When operated in a multipass mode, the system exhibits a practical and efficient way of mixing particles.